Development of human sensory mimicking system - Nazifah, Ahmad Fikri; Ali Yeon, Md Shakaff, Prof. Dr.; Abdul Hamid, Adom, Prof. Madya Dr.; Mohd Noor, Ahmad, Prof. Dr.; Abu Hassan, Abdullah; Ammar, Zakaria; M. A., Markom (American Scientific Publishers, 2012)
Link to publisher's homepage at http://www.aspbs.com/